INCOME OVER FEED COST FOR SMALL- TO MEDIUM-SCALE BEEF CATTLE FATTENING OPERATIONS IN EAST JAVA - Priyanti, A.; Mahendri, I.G.A.P.; Cahyadi, F.; Cramb, R.A. (Journal of the Indonesian Tropical Animal Agriculture, 2012)
An evaluation was conducted of the returns to fattening cattle of small- and medium-scaleenterprises in East Java. The objective was to analyze income over feed costs (IOFC) based on locallyavailable feedstuffs to increase liveweight gain. The study was conducted during July-September 2010and January-March 2011, representing relative dry and wet season. The breeds were PO and Limousinand Simmental crossed with PO (LimPO and SimPO). Small-scale farmers owning 1-2 bulls andmedium-scale farmers fattening 10-20 bulls in one period. Fattening period was 58 and 46 days,respectively for dry and wet season. Monthly measurements included liveweight, feed intake, input andoutput prices. Mean values of growth rates and IOFC were compared using t-tests. The results indicatedthat, for small-scale operations, SimPO bulls gave a significantly higher return than either PO or LimPObulls. Likewise, LimPO gave a higher IOFC than SimPO in medium-scale operations. Small-scalefarmers achieved equal or higher IOFC for European-cross than medium-scale farmers in both seasons.This reflects that cash outlays for feed were about two-thirds that of medium-scale operations whiledaily growth rates were similar. Small-scale fattening operations using European-cross can befinancially competitive with medium-scale operations in both wet and dry seasons.